A solid-state lithium battery and a method for preparing the same

By directly preparing the organic polymer porous membrane support frame and composite solid electrolyte matrix on the positive electrode layer of the solid lithium battery, an ultra-thin composite solid electrolyte layer is formed, which solves the safety and mechanical properties of traditional lithium-ion batteries and achieves a solid lithium battery with high energy density and cycle stability.

CN113471542BActive Publication Date: 2025-05-02THE HONG KONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110536488.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-17
Publication Date
2025-05-02
Estimated Expiration
2041-05-17

AI Technical Summary

Technical Problem

The liquid electrolyte used in traditional lithium-ion batteries has the risk of fire and explosion, and the mechanical properties of solid electrolytes are poor, making it difficult to thin the battery thickness, affecting energy density and cycling stability. At the same time, the existing preparation methods of solid-state lithium batteries lead to poor interface contact between the solid-state electrolyte and the electrode, which increases the internal resistance of the battery.

Method used

Using an integrated positive electrode/ultra-thin composite solid electrolyte layer structure, an ultra-thin and solid electrolyte matrix is ​​directly prepared on the positive electrode layer to form an ultra-thin and solid electrolyte layer, improving the interface contact between the electrode and the electrolyte and enhancing the mechanical properties of the electrolyte.

Benefits of technology

It significantly reduces the internal resistance of the battery, improves the energy density and cycle stability of the battery, enhances the safety and life of the battery, and simplifies the battery preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003070042080000011
    Figure HDA0003070042080000011
  • Figure HDA0003070042080000012
    Figure HDA0003070042080000012
  • Figure HDA0003070042080000021
    Figure HDA0003070042080000021
Patent Text Reader

Abstract

The present invention relates to the field of electrochemical energy storage, and specifically refers to a solid-state lithium battery and a preparation method thereof. The solid-state lithium battery comprises an integrated positive electrode / ultra-thin composite solid electrolyte layer and a negative electrode layer, wherein: the positive electrode layer comprises a positive electrode active material, a binder and an electronic conductor, and the ultra-thin composite solid electrolyte layer comprises a supporting frame and a composite solid electrolyte matrix, and the composite solid electrolyte matrix is ​​directly prepared on the positive electrode layer to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer. The battery preparation process provided by the present invention can not only ensure good contact between the electrode and the solid electrolyte, but also effectively reduce the thickness of the composite solid electrolyte layer and enhance its mechanical properties, effectively improve the safety, stability and energy density of the battery, and simplify the preparation process of the solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical energy storage, and in particular to a solid-state lithium battery and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of electric vehicles, portable electronic devices and large-scale energy storage, the research and development of a new generation of high energy density, high safety and high stability batteries has received widespread attention from academia and industry. The flammable electrolyte used in traditional lithium-ion batteries leads to the risk of battery fire or even explosion, which poses a serious safety hazard. Replacing the liquid electrolyte with a solid electrolyte with extremely high thermal stability can greatly improve the battery safety problem and help to further improve the battery energy density. The composite solid electrolyte composed of ceramic filler, polymer conductive matrix, and lithium salt has the advantage of easy processing, but its poor mechanical properties make it difficult to reduce its thickness, which is not conducive to improving the battery energy density and cycle stability. In addition, the current solid-state lithium battery usually prepares the solid electrolyte and electrode separately, and then assembles the parts together. This method will result in extremely poor interface contact between the solid electrolyte and the electrode, resulting in a large battery internal resistance, which restricts the practical application of solid-state lithium batteries. Therefore, it is necessary to develop a solid electrolyte with better performance and a preparation method suitable for solid-state lithium batteries to achieve solid-state lithium batteries with high energy density, high stability and safety. Summary of the invention

[0003] The purpose of the present invention is to provide a solid-state lithium battery and a preparation method thereof, which can not only ensure good contact between the electrode and the solid electrolyte, but also effectively reduce the thickness of the composite solid electrolyte layer and enhance its mechanical properties, effectively improve the safety, life and energy density of the battery, and simplify the battery preparation process.

[0004] In order to achieve the above object, the technical solution of the present invention is:

[0005] A solid-state lithium battery, comprising an integrated positive electrode / ultra-thin composite solid electrolyte layer and a negative electrode layer; wherein: the positive electrode layer comprises a positive electrode active material, a binder and an electronic conductor; the ultra-thin composite solid electrolyte layer comprises a supporting frame and a composite solid electrolyte matrix; the ultra-thin composite solid electrolyte layer is directly prepared on the positive electrode layer to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer.

[0006] The solid-state lithium battery, in terms of weight percentage, has 60-96% of the positive electrode active material in the positive electrode layer, 2-20% of the binder, and 2-20% of the electronic conductor; wherein:

[0007] The positive electrode active material is LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiMn2O4, LiCoO2, LiNiO2, LiNi 1-2x Co x Mn x O2, S or Li2S; LiNi 1-2x Co x Mn x O2, 0 <X<1 / 2;

[0008] The binder is one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl ethylene carbonate (PPC), and polyacrylonitrile (PAN);

[0009] The electronic conductor is one or more of conductive carbon black, acetylene black, Ketjen black or other carbon-based conductive materials.

[0010] The solid-state lithium battery has a lithium salt added to the binder in an amount of 10-40% by mass of the binder as required, wherein the lithium salt is one or more of a lithium-containing inorganic salt and a lithium-containing organic salt.

[0011] In the solid-state lithium battery, the support frame material of the ultra-thin composite solid electrolyte layer is an organic polymer porous membrane, comprising one or more of the following materials: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), polybenzimidazole (PBI), polyimide (PI), polymethyl methacrylate (PMMA) or polytetrafluoroethylene (PTFE), the support frame thickness is less than 20 microns, the porosity is 50-95%, and the average pore size is 0.1-5 microns.

[0012] The solid-state lithium battery, in terms of weight percentage, has a composite solid electrolyte matrix of an ultra-thin composite solid electrolyte layer comprising: 5-80% ceramic filler, 10-85% polymer conductive matrix, and 10-40% lithium salt, wherein:

[0013] The ceramic filler is one or more of oxide ceramics, sulfide ceramics and halide ceramics;

[0014] The polymer conductive matrix is ​​one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethylethylene carbonate (PPC), polyacrylonitrile (PAN), and polymethyl methacrylate (PMMA);

[0015] The lithium salt is one or more of a lithium-containing inorganic salt and a lithium-containing organic salt.

[0016] The method for preparing the solid-state lithium battery comprises the following steps:

[0017] (a) uniformly mixing a positive electrode material comprising a positive electrode active material, a binder and an electronic conductor to prepare a positive electrode layer on a conductive substrate;

[0018] (b) preparing an ultra-thin composite solid electrolyte layer support frame with a thickness of less than 20 microns on the positive electrode layer obtained in step (a);

[0019] (c) dissolving and dispersing a composite solid electrolyte matrix material comprising a ceramic filler, a polymer conductive matrix and a lithium salt in an organic solvent to obtain a precursor slurry of the composite solid electrolyte matrix, and casting the precursor slurry in the support frame obtained in step (b), and after the organic solvent is dried, an integrated positive electrode / ultra-thin composite solid electrolyte layer is obtained;

[0020] (d) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer and the negative electrode layer obtained in step (c) and subjecting them to heat treatment and / or mechanical compression to obtain the solid-state lithium battery.

[0021] The preparation method of the solid-state lithium battery comprises the following steps: in step (a), the positive electrode active material, the binder and the electronic conductor are mixed with the organic solvent to form a positive electrode slurry, so that the solid content in the positive electrode slurry is 20 to 80 wt %; the positive electrode slurry is coated on the current collector aluminum foil, and the positive electrode slurry is dried to obtain a positive electrode layer, the thickness of which is 10 to 80 microns.

[0022] In the method for preparing the solid-state lithium battery, in step (b), the organic polymer porous membrane serving as the support frame of the ultra-thin composite solid electrolyte layer is directly prepared on the positive electrode layer by electrospinning or hot pressing.

[0023] In the method for preparing a solid-state lithium battery, in step (c), the solid content of the precursor slurry is 2 to 50 wt %.

[0024] In the preparation method of the solid-state lithium battery, in step (c), after pouring the precursor slurry, it is heated and dried in a vacuum oven at a temperature of 30 to 150° C. for 12 to 48 hours, and the thickness of the ultra-thin composite solid electrolyte layer is 5 to 20 microns.

[0025] The design idea of ​​the present invention is:

[0026] The present invention realizes continuous ion conduction at the cathode / electrolyte interface and the entire cathode by directly manufacturing an ultra-thin and strong porous organic network-supported solid electrolyte on the cathode, thereby significantly reducing the interface resistance and increasing the cathode loading. At the same time, due to the strengthening effect of the porous organic framework, an ultra-thin solid electrolyte with super strong dendrite suppression ability can be achieved, which is beneficial to improving the cycle stability and energy density of the battery. The present invention is suitable for large-scale solid-state battery production.

[0027] The present invention has the following advantages and beneficial effects:

[0028] 1. The present invention directly prepares an ultra-thin composite solid electrolyte layer reinforced by a polymer porous membrane on the positive electrode layer, which not only greatly improves the interface contact problem between the electrode and the solid electrolyte and reduces the internal resistance of the battery, but also benefits from the supporting effect of the polymer porous membrane. The mechanical strength of the electrolyte is greatly improved, thereby effectively reducing the thickness of the electrolyte and improving the energy density and cycle performance of the battery.

[0029] 2. The present invention simplifies the preparation process of solid-state lithium batteries, which is simple, fast, high-yield, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 (a) is a surface electron micrograph of a porous polyvinylidene fluoride (PVDF) fiber layer serving as a supporting framework for an ultrathin composite solid electrolyte layer. Figure 1 (b) is a surface electron micrograph of a composite solid electrolyte matrix supported by a porous fiber layer of polyvinylidene fluoride (PVDF).

[0031] Figure 2 This is a cross-sectional electron microscope image of an integrated positive electrode / ultra-thin composite solid electrolyte layer. 1 is the ultra-thin composite solid electrolyte layer; 2 is the positive electrode layer.

[0032] Figure 3 is the charge and discharge curve of the solid-state lithium battery of Example 1. In the figure, the horizontal axis Specific capacity represents the specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V).

[0033] Figure 4 is the charge and discharge curve of the solid-state lithium battery of Example 2. In the figure, the horizontal axis Specific capacity represents the specific capacity (mAh g -1 ), the vertical axis Voltage represents voltage (V). DETAILED DESCRIPTION

[0034] In the specific implementation process, the solid-state lithium battery of the present invention comprises an integrated positive electrode / ultra-thin composite solid electrolyte layer and a negative electrode layer; the positive electrode layer comprises a positive electrode active material, a binder and an electronic conductor; the ultra-thin composite solid electrolyte layer comprises a supporting frame and a composite solid electrolyte matrix, and is directly prepared on the positive electrode layer to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer.

[0035] The method for preparing a solid-state lithium battery of the present invention comprises the following consecutive steps: a) preparing a positive electrode material on a conductive substrate to obtain a positive electrode layer; b) directly preparing an ultra-thin composite solid electrolyte layer support frame with a thickness of less than 20 microns on the positive electrode layer obtained in step a); c) pouring and curing the precursor slurry of the composite solid electrolyte matrix in the support frame prepared in step b) to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer; d) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer obtained in step c) with a negative electrode layer, and performing heat treatment or mechanical compression to obtain a solid-state lithium battery.

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] Embodiment 1:

[0039] The specific preparation process of the solid-state lithium battery of this embodiment is as follows:

[0040] (1) 0.8 g of lithium iron phosphate positive electrode powder, 0.06 g of polyethylene oxide (PEO) binder, 0.02 g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 0.1 g of conductive carbon black were uniformly dispersed in 2 ml of N,N-dimethylformamide (DMF) solvent, and magnetically stirred for 12 h to obtain a positive electrode slurry; the positive electrode slurry was coated on a current collector aluminum foil, and the positive electrode slurry was dried at 60° C. for 48 h to obtain a positive electrode layer with a thickness of 30 μm;

[0041] (2) Dissolve polyvinylidene fluoride (PVDF) in a mixed solvent of dimethyl sulfoxide (DMSO) and acetone in a volume ratio of 1:1, and prepare it directly on the positive electrode layer obtained in step (1) by electrospinning to obtain a polyvinylidene fluoride (PVDF) porous fiber layer as an ultra-thin composite solid electrolyte layer support frame. The applied voltage of electrospinning is 19 kV, the support frame thickness is 17 microns, the porosity is 80%, and the average pore size is 3 microns.

[0042] (3) Weigh 0.6g polyethylene oxide (PEO), 0.2g lithium lanthanum zirconium oxide (LLZO) ceramic, and 0.3g lithium bis(trifluoromethanesulfonyl)imide (LiTFS), evenly disperse them in 10ml acetonitrile solution, and stir for 12 hours to obtain a precursor slurry for the composite solid electrolyte matrix. Then pour the obtained slurry into the electrolyte support frame polyvinylidene fluoride (PVDF) porous fiber layer obtained in step (2). In this process, the precursor slurry of the composite solid electrolyte matrix will fully infiltrate the positive electrode interface. Place it in a vacuum oven at 65°C and dry it for 48 hours. After the solvent evaporates, an integrated positive electrode / ultra-thin composite solid electrolyte layer is obtained. The thickness of the ultra-thin composite solid electrolyte layer is 17 microns.

[0043] (4) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer obtained in step (3) with the lithium metal negative electrode, and hot pressing for 10 min at a temperature of 60° C. and a pressure of 10 MPa to obtain a solid-state lithium battery with high energy density and high safety.

[0044] The structure and performance of the solid-state lithium battery of this embodiment will be characterized as follows:

[0045] like Figure 1 As shown in (a), the surface electron micrograph of the polyvinylidene fluoride (PVDF) porous fiber layer prepared in step (2) as the supporting frame of the ultra-thin composite solid electrolyte layer is Figure 1 (a) It can be seen that the fiber diameter is about 0.8 μm.

[0046] like Figure 1 (b) shows a surface electron micrograph of the composite solid electrolyte matrix supported by the polyvinylidene fluoride (PVDF) porous fiber layer prepared in step (3), Figure 1 (b) It can be seen that the electrolyte surface is smooth and flat, which is conducive to the cycle stability of the battery.

[0047] like Figure 2 As shown in Figure 1, the cross-sectional electron microscope image of the integrated positive electrode / ultra-thin composite solid electrolyte layer. 1 is the ultra-thin composite solid electrolyte layer, which is 17 microns thick; 2 is the positive electrode layer. Figure 2 It can be seen that the positive electrode has good contact with the solid electrolyte, and the pores in the positive electrode layer are also filled with the solid electrolyte, which is conducive to the continuous and rapid transmission of ions.

[0048] like Figure 3 As shown in the figure, the charge and discharge curve of the solid-state lithium battery shows that the curve of the battery is similar to the theoretical curve of lithium / lithium iron phosphate, and its specific capacity can reach 164mAh g -1 .

[0049] Embodiment 2:

[0050] The specific preparation process of the solid-state lithium battery of this embodiment is as follows:

[0051] (1) 0.8 g of LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM111) lithium-ion battery positive electrode material powder, 0.1g polyvinylidene fluoride (PVDF) binder and 0.1g conductive carbon black are uniformly dispersed in 1.5ml N-methyl-2-pyrrolidone (NMP) solvent, and magnetically stirred for 6h to obtain positive electrode slurry; the positive electrode slurry is coated on the current collector aluminum foil, and the positive electrode slurry is dried at 80°C for 48h to obtain a positive electrode layer with a thickness of 50 microns;

[0052] (2) The polyimide porous membrane is hot-pressed on the positive electrode layer obtained in step (1) to serve as a support frame for the ultra-thin composite solid electrolyte layer. The hot-pressing temperature is 80 degrees Celsius, the hot-pressing pressure is 10 MPa, the hot-pressing time is 3 minutes, the support frame thickness is 10 microns, the porosity is 75%, and the average pore size is 1 micron.

[0053] (3) Weigh 0.6g of polyvinylidene fluoride (PVDF), 0.2g of lithium lanthanum zirconium oxide (LLZO) ceramic, and 0.2g of lithium bis(trifluoromethanesulfonyl)imide (LiTFS) and evenly disperse them in 10ml of N,N-dimethylformamide (DMF) solution, and stir for 12 hours to obtain a precursor slurry for the composite solid electrolyte matrix. Then pour the obtained slurry into the supporting frame polyimide porous layer obtained in step (2). In this process, the precursor slurry of the composite solid electrolyte matrix will fully infiltrate the positive electrode interface. Place it in a vacuum oven and dry it at 65°C for 12 hours to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer, and the thickness of the ultra-thin composite solid electrolyte layer is 10 microns.

[0054] (4) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer obtained in step (3) with the lithium metal negative electrode, and hot pressing for 10 min at a temperature of 60° C. and a pressure of 15 MPa to obtain a solid-state lithium battery with high energy density and high safety.

[0055] like Figure 4As shown in the figure, the charge and discharge curves of the solid-state lithium battery show that the curve of the battery is similar to the theoretical curve of lithium / NCM111, and its specific capacity can reach 180 mAh g -1 .

[0056] The results of the embodiments show that the battery preparation process provided by the present invention can not only ensure good contact between the electrode and the solid electrolyte, but also effectively reduce the thickness of the composite solid electrolyte layer and enhance its mechanical properties, effectively improve the safety, stability and energy density of the battery, and simplify the preparation process of the solid-state lithium battery.

Claims

1. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises an integrated positive electrode / ultra-thin composite solid electrolyte layer and a negative electrode layer; wherein: the positive electrode layer comprises a positive electrode active material, a binder and an electronic conductor; the ultra-thin composite solid electrolyte layer comprises a support frame and a composite solid electrolyte matrix; the ultra-thin composite solid electrolyte layer is directly prepared on the positive electrode layer to obtain an integrated positive electrode / ultra-thin composite solid electrolyte layer; The support frame material of the ultra-thin composite solid electrolyte layer is an organic polymer porous membrane, comprising one or more of the following materials: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), polybenzimidazole (PBI), polyimide (PI), polymethyl methacrylate (PMMA) or polytetrafluoroethylene (PTFE), the support frame thickness is less than 20 microns, the porosity is 50-95%, and the average pore size is 0.1-5 microns; The composite solid electrolyte matrix of the ultra-thin composite solid electrolyte layer comprises, by weight percentage: 5-80% ceramic filler, 10-85% polymer conductive matrix, and 10-40% lithium salt, wherein: The ceramic filler is one or more of oxide ceramics, sulfide ceramics and halide ceramics; The polymer conductive matrix is ​​one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethylethylene carbonate (PPC), polyacrylonitrile (PAN), and polymethyl methacrylate (PMMA); The lithium salt is one or more of a lithium-containing inorganic salt and a lithium-containing organic salt; The method for preparing the solid-state lithium battery comprises the following steps: (a) uniformly mixing a positive electrode material comprising a positive electrode active material, a binder and an electronic conductor to prepare a positive electrode layer on a conductive substrate; (b) preparing an ultra-thin composite solid electrolyte layer support frame with a thickness of less than 20 microns on the positive electrode layer obtained in step (a); the organic polymer porous membrane serving as the ultra-thin composite solid electrolyte layer support frame is directly prepared on the positive electrode layer by electrospinning or hot pressing; (c) dissolving and dispersing a composite solid electrolyte matrix material comprising a ceramic filler, a polymer conductive matrix and a lithium salt in an organic solvent to obtain a precursor slurry of the composite solid electrolyte matrix, and casting the precursor slurry in the support frame obtained in step (b), and after the organic solvent is dried, an integrated positive electrode / ultra-thin composite solid electrolyte layer is obtained; (d) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer and the negative electrode layer obtained in step (c) and subjecting them to heat treatment and / or mechanical compression to obtain the solid-state lithium battery.

2. The solid-state lithium battery according to claim 1, characterized in that: In terms of weight percentage, the positive electrode active material in the positive electrode layer is 60-96%, the binder is 2-20%, and the electronic conductor is 2-20%; wherein: The positive electrode active material is LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, Li3V2(PO4)3, LiMn2O4, LiCoO2, LiNiO2, LiNi 1-2x Co x Mn x O2, S or Li2S; The binder is one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polymethyl ethylene carbonate (PPC), and polyacrylonitrile (PAN); The electronic conductor is one or more of conductive carbon black, acetylene black, Ketjen black or other carbon-based conductive materials.

3. The solid-state lithium battery according to claim 2, characterized in that: According to the need, a lithium salt accounting for 10-40% of the binder mass fraction is added to the binder, and the lithium salt is one or more of a lithium-containing inorganic salt and a lithium-containing organic salt.

4. The method for preparing a solid-state lithium battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: (a) uniformly mixing a positive electrode material comprising a positive electrode active material, a binder and an electronic conductor to prepare a positive electrode layer on a conductive substrate; (b) preparing an ultra-thin composite solid electrolyte layer support frame with a thickness of less than 20 microns on the positive electrode layer obtained in step (a); the organic polymer porous membrane serving as the ultra-thin composite solid electrolyte layer support frame is directly prepared on the positive electrode layer by electrospinning or hot pressing; (c) dissolving and dispersing a composite solid electrolyte matrix material comprising a ceramic filler, a polymer conductive matrix and a lithium salt in an organic solvent to obtain a precursor slurry of the composite solid electrolyte matrix, and casting the precursor slurry in the support frame obtained in step (b), and after the organic solvent is dried, an integrated positive electrode / ultra-thin composite solid electrolyte layer is obtained; (d) stacking the integrated positive electrode / ultra-thin composite solid electrolyte layer and the negative electrode layer obtained in step (c) and subjecting them to heat treatment and / or mechanical compression to obtain the solid-state lithium battery.

5. The method for preparing a solid-state lithium battery according to claim 4, characterized in that: In step (a), the positive electrode active material, the binder and the electronic conductor are mixed with the organic solvent to form a positive electrode slurry, so that the solid content in the positive electrode slurry is 20 to 80 wt %; the positive electrode slurry is coated on the current collector aluminum foil, and the positive electrode slurry is dried to obtain a positive electrode layer with a thickness of 10 to 80 microns.

6. The method for preparing a solid-state lithium battery according to claim 4, characterized in that: In step (c), the solid content of the precursor slurry is 2 to 50 wt %.

7. The method for preparing a solid-state lithium battery according to claim 4, characterized in that: In step (c), after pouring the precursor slurry, it is heated and dried in a vacuum oven at a temperature of 30 to 150° C. for 12 to 48 hours, and the thickness of the ultra-thin composite solid electrolyte layer is 5 to 20 microns.

Citation Information

Patent Citations

  • Solid-state lithium battery and preparation method thereof

    CN112421103A

  • Thin film type solid electrolyte composite sheet and all-solid-state lithium secondary battery comprising the same

    KR101946381B1